L’Atlas des Régions Naturelles, un manifeste photoconceptuel de la périphérie ordinaire - Raphaële Bertho (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Initiated in 2017 by Eric Tabuchi, L’Atlas des Régions Naturelles seeks to devote an unprecedented place for photography within architectural or landscape projects. Here, the image is not summoned using order; the purpose of its very existence is to stimulate the project. Heir to the picturesque voyages of the 19th century, American conceptualism of the 1960s, contemporary French photography projects, architectural manifestos from the end of the twentieth century, the thought of the vernacular landscape as well as the theorization of the ordinary, the aim is to try to identify this original visual object. Analyses of the adopted protocol and exposure strategies make it possible to understand the project of Eric Tabuchi, both as a manifesto of the periphery and as a proposal for the intellectual engineering of the apprehension of current territories.